EARLY WARNING SYSTEM DAN HARGA SAHAM PERUSAHAAN ASURANSI - Devina Nasywa Kusuma; Nina Karina Karim (BORJUIS: JURNAL OF ECONOMY, 2024)
This study aims to determine the impact of Early Warning System (EWS) ratios on the stock prices of insurance companies. The population in this study consists of insurance companies listed on the Indonesia Stock Exchange (IDX). The sample was determined using purposive sampling technique, resulting in 15 insurance companies as samples. This study is associative in nature with a quantitative approach. The data analysis method employs multiple linear regression with the aid of the SPSS 29 software. The EWS ratios used in this study include Solvency Ratio, Claims Expense Ratio, Investment Return Ratio, Liquidity Ratio, Premium Growth Ratio, and Underwriting Ratio. The results of the study indicate that the Solvency Ratio, Investment Return Ratio, and Liquidity Ratio positively affect the stock prices of insurance companies, whereas the Claims Expense Ratio, Premium Growth Ratio, and Underwriting Ratio negatively affect the stock prices of insurance companies.